The Role of Packaging, Price, and Digital Marketing in Increasing MSME’s Sales - Decky Hendarsyah; Febrianty, Nirvana Annisa’; Bahri, Saiful (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research aims to examine the influence of packaging, price, and digital marketing on increasing MSME (Micro, Small, and Medium Enterprises) sales. Using a descriptive quantitative approach, this study collects primary data through questionnaires and interviews, as well as secondary data from literature sources. The questionnaires serve as the primary data source, while interviews provide supporting data. The research population includes all MSMEs supported by KADIN in Bengkalis sub-district, Bengkalis district. A random sampling technique was applied, with a total of 104 respondents selected for the study. The data analysis was conducted using multiple linear regression with the help of SPSS software. This analysis involved testing validity, reliability, classical assumptions, and hypotheses to ensure the accuracy and consistency of the data. The results of the research indicate that both packaging and price have a positive and significant effect on increasing MSME sales. In contrast, digital marketing did not show a significant effect on boosting sales. Among the three factors, packaging emerged as the most dominant factor influencing the increase in sales. This study adds value to existing theories by confirming the importance of packaging and price in enhancing MSME sales performance. It also offers practical implications for the government and MSME stakeholders. For the government, the findings can be used to develop strategies and policies that support MSMEs, particularly in areas related to packaging and pricing strategies. For MSME owners and entrepreneurs, this research provides insights into key aspects of business operations that can be optimized to improve sales. By focusing on packaging and pricing strategies, MSMEs can enhance their competitiveness in the market, leading to increased sales and long-term business success.